2019
DOI: 10.2174/1385272823666190916144235
|View full text |Cite
|
Sign up to set email alerts
|

Green and Facile Synthesis of Pyrimidine Derivatives Using Choline Chloride-urea Mixture as a Deep Eutectic Solvent or Cerium (IV) Ammonium Nitrate

Abstract: An efficient and facile synthesis of substituted pyrimidine derivatives through Biginelli type reaction was achieved in high yields via one-pot reaction of aromatic aldehydes, active methylene compounds and urea or thiourea in the presence of choline chloride- urea mixture as a deep eutectic solvent or cerium (IV) ammonium nitrate (CAN) as a catalyst at different conditions. The reaction was carried out using different ratio of CAN in different solvents to determine the optimum conditions. In addition, 2-merca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Recently, deep eutectic solvents (DESs) have appeared in green chemistry as promising alternatives to other organic solvents due to their low volatility, nonflammability and high thermal stability which promote their uses in many organic transformations and reactions (1)(2)(3)(4)(5). Additionally, DESs have the advantages of being recyclable and inexpensive can be used in stoichiometric amounts as catalyst (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, deep eutectic solvents (DESs) have appeared in green chemistry as promising alternatives to other organic solvents due to their low volatility, nonflammability and high thermal stability which promote their uses in many organic transformations and reactions (1)(2)(3)(4)(5). Additionally, DESs have the advantages of being recyclable and inexpensive can be used in stoichiometric amounts as catalyst (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, deep eutectic solvents (DESs) have attracted great attention as green solvents in many organic reactions and transformations [1][2][3][4][5][6][7][8]. DESs can be easily formulated via hydrogen bonding between two components, the first is hydrogen bond donor which can be acid [9], alcohol [10,11] carbohydrate [12] or amide [13,14] and the second is hydrogen bond acceptor as quaternary ammonium salt [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Abbott et al reported facile synthesis of eutectic liquid from choline chloride [ (2-hydroxyethyl) trimethylammonium chloride] and urea as renewable starting materials in a molar ratio of 1:2 showing interesting solvent properties and a melting point lower than those of the individual components. [15] On the other hand, 1,3-benzoxazine derivatives (BZs) are one of the most important heterocycles owing to their remarkable antibacterial and antifungal activities, [16][17][18] anticancer, [19,20] analgesic, [21] antiplatlet, [22] and antimycobacterial activity. [15] On the other hand, 1,3-benzoxazine derivatives (BZs) are one of the most important heterocycles owing to their remarkable antibacterial and antifungal activities, [16][17][18] anticancer, [19,20] analgesic, [21] antiplatlet, [22] and antimycobacterial activity.…”
Section: Introductionmentioning
confidence: 99%